Schaum's Outline of Discrete Mathematics, Fourth Edition - Lipschutz, Seymour; Lipson, Marc (McGraw-Hill's AccessEngineering., 2022)
Study smarter and stay on top of your discrete mathematics course with the bestselling Schaum's Outline-now with the new Schaum's app and website!. Schaum's Outline of Discrete Mathematics, Fourth Edition is the go-to study guide for more than 115,000 math majors and first- and second-year university students taking basic computer science courses. With an outline format that facilitates quick and easy review, Schaum's Outline of Discrete Mathematics, Fourth Edition helps you understand basic concepts and get the extra practice you need to excel in these courses. Coverage includes set theory; relations; functions and algorithms; logic and propositional calculus; counting; advanced counting techniques, recursion; probability; graph theory; directed graphs; binary trees; properties of the integers; languages, automata, grammars; finite state machines and Turing machines; ordered sets and lattices, and Boolean algebra.